DESIGNING A TEACHING-LEARNING BASED ON LANDAMATICS IN COMPUTER ARCHITECTURE AND ITS EFFECT IN ACHIEVEMENTDESIGNING A TEACHING-LEARNING BASED ON LANDAMATICS IN COMPUTER ARCHITECTURE AND ITS EFFECT IN ACHIEVEMENT - F, Dr. Riyadh; Sheraa, Hameed Al; Abdul-kader, Sameera A (MAGISTRA, 2013)
Computer architecture is important and difficult subject in computer department, so it needs always to learn and teach it carefully and in more interest. This is because computer architecture deals with software and hardware, and it needs theoretical and practical aspects. The research has aimed to prepare a teaching according to Landa theory in computer architecture subject and check its effect on achievement of the student of 2nd stage in computer department of Education College in Diyala University. This research deals with designing a learning system for teaching computer architecture. In this project the sample was (74) students divided into two groups (38) as experimental and (36) as control. The researchers tool was an achievement test containing (15) items to estimate the levels of Meril classification â remember, use, and explorationâ. The result which used T-test that Experimental group that had learned according to Landamatics scores more than Control group in achievement test. Hence that it was concluded that the knowledge orientation in the organized educational activities that were organized